Younger pubertal age is associated with allergy and other atopic conditions in girls. Issue 8 (29th December 2014) - Hong, Chi‐Chen; Pajak, Ashley; Teitelbaum, Susan L.; Vangeepuram, Nita; Galvez, Maida; Pinney, Susan M.; Windham, Gayle; Kushi, Lawrence H.; Biro, Frank M.; Wolff, Mary S.; the Breast Cancer; Environment Research Program
Abstract Background Early menarche is linked to higher incidence of adult asthma, suggesting that earlier puberty may influence type 2 immune response characteristics of allergic diseases. We examined the hypothesis that timing of breast and pubic hair development, which precede menarche, is associated with increased childhood atopic conditions. Methods Girls were enrolled at 6–8 yr of age (2004–2007) in the Breast Cancer and the Environment Research Program Puberty Study and were followed through 2011. Pubertal stages were assessed and atopic conditions were queried annually. Associations of age at pubertal stage 2 for breast or pubic hair development with atopic conditions were assessed using prevalence ratios (PR) or odds ratios (OR) and 95% confidence intervals (CI) from log‐binomial regression and generalized estimating equation models, controlling for body mass index and other covariates. A total of 1055 girls with medical and pubertal stage data were included. Results Asthma (ever vs. never) was associated with younger pubarche (≤10 vs. >10 yr, PR = 1.15, CI: 1.04–1.28 adjusted for race/ethnicity and site; PR = 1.13, CI: 1.01–1.25 further adjusted for BMI), but not thelarche. In longitudinal models, risk of developing allergies increased with younger age at pubarche (adjusted OR = 1.60, CI: 1.10–2.34; ≤10 vs. >10 yr). Risks were highest among black girls with earlier pubarche (n = 248/326); for allergies, their fully adjusted OR was 2.35, CI: 1.06–5.19 for pubarche ≤10 vs. >10 yr. Conclusions Atopic conditions during childhood are associated with younger age at pubarche, independent of obesity, and these relationships may vary by racial/ethnic groups.